Analysis of the effects of domestic waste disposal methods on mucilage with life cycle assessment - Bilgili, Levent; Cetinkaya, Afsin Yusuf; Sari, Mustafa (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Mucilage has been observed surface and water column of the Sea of Marmara since 2021 and the domestic and industrial based organic waste is accepted as one of the major sources for the mucilage. In this study, in order to measure the impacts of the wastes to mucilage, seven different waste disposal scenarios, which are determined according to EU directives, are applied to the waste composition of municipalities located near the Sea of Marmara. Then, the environmental impacts of these scenarios are calculated in life cycle perspective. Results show that composting has the greatest positive impact via reducing the deleterious impacts of organic wastes, which are the major source for nutritious groundwater. As to the authors knowledge, this is the first study to integrate life cycle assessment, waste management, and mucilage. The results can be used to guide municipalities around the Sea of Marmara on the prevention of mucilage.
Keywords: Mucilage Sea of Marmara; Life cycle assessment; Domestic waste; Compost; ADRIATIC SEA; ASSESSMENT LCA; MARINE MUCILAGES; MANAGEMENT; STRATEGIES; COMMUNITY; DYNAMICS; PATTERNS; IMPACTS; MARMARA; Environmental Sciences & Ecology; Marine & Freshwater Biology